Evaluating alternatives to zinc oxide or antibiotics in nursery pig diets - Eickleberry, Caitlyn R.; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
There is increasing consumer pressure to reduce the use of antimicrobials and ZnO in swine diets for health and environmental reasons, but thus far, research has shown few possible alternatives. In this study, medium chain fatty acids (MCFA) were compared to ZnO and carbadox for their overall efficacy on nursery pig performance. There was a total of 360 (DNA 200x400; 5.4±0.06 kg BW) nursery pigs weaned at 21d. At weaning, pigs were assigned to one of 60 pens (6 pigs/pen) resulting in 10 replicates in a complete randomized design. There were 6 treatments: 1.) control; 2.) 3,000 ppm ZnO phase 1, 1,500 ppm ZnO phase 2; 3.) 50 g/ton carbadox; 4.) 1% blend of C6:C8:C10; 5.) 1% Feed Energy R2 (Feed Energy Corp, Des Moines, IA); 6.) 1% FORMI GML (ADDCON, Bitterfeld-Wolfen, Germany). Common diets were provided on 20d to 35. Individual pig weights, feeder weights, and pounds of feed added were documented for each pen weekly. Data was analyzed using the SAS glimmix program with P<0.05. For the treatment phase of the study (0d to 19d), pigs fed ZnO, carbadox, or 1% FORMI had greater ADG compared to the control and the other MCFAs (P<0.0001). During this period, there was also difference in ADFI between pigs fed ZnO or those fed the control, MCFA, or 1% FORMI diets (P=0.0004). During the common phase there was no detected difference amongst the treatments for ADG (P=0.873), ADFI (P=0.089), and G:F (P= 0.158). In conclusion 1% FORMI had similar performance as ZnO and carbadox while the other tested MCFA may require additional research.
Keywords: Spring 2019